Daya Saing dan Faktor-Faktor yang Mempengaruhi Ekspor di Provinsi Bali - PUTU CENDANA FIRJIONITA; MADE ANTARA; I MADE SUDARMA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Competitiveness and Factors Affecting Vanilli Exports in Bali Province Plantation has a strategic position in the development of the agricultural sector in Bali. One of the main export products from plantations is vanilla. Vanilla is a plant species of high economic value with relatively stable price fluctuation. The decline in the volume of vanilla exports is caused by the difficulty and maintenance of vanilla plants, which causes vanilla farmers to choose to plant annual crops and manipulate prices from exporters. The purpose of this study is to find out the competitiveness of vanilla commodity exports in Bali Province and factors that simultaneously and partially influence vanilla commodity exports in Bali Province. The study was conducted using Revealed Comparative Advantage (RCA) to identify the competitiveness of vanilla commodity exports in the Province of Bali. Multiple Linear Regression Analysis is used to determine the 4 variables, namely production, the US dollar exchange rate, inflation and prices, and variables that affect vanilla exports. The RCA index test results show that vanilla commodity does not yet have the competitiveness or the RCA index produced is less than one. The results of the multiple linear regression test show that of the 4 variables namely production, the US dollar exchange rate, inflation and prices, only the production variable has a significant effect on vanilla exports in the Province of Bali.